Retail internationalization and ist impact on the Russian agri - food business - Jon Hanf; Vera Belaya (Journal for East European Management Studies, 2008)
The internationalization process of the retailing sector is still in its turbulent starting phase. The present process of retail internationalization has created new trends in the agri-food sector such as global sourcing and retail branding. The example of Metro Group Russia underlines this point. The introduction and implementation of supply chain management concepts affect Russian agri-food business. Therefore, the aim of our article is to analyze this development. We outline the internationalization process of the retail business,and then we elaborate on the structural changes. Second, we apply this knowledge to the Russian agri-food business. We also discuss the future prospects and outlook on further development of the Russian food sector in the context of retail internationalization. – – Der Internationalisierungsprozess des Einzelhandelssektors ist nach wie vor in einer unruhigen Startphase. Der Prozess der Internationalisierung des Einzelhandels hat Tendenzen wie Global Sourcing und Retail Branding im Agrar- uns Ernährungssektor katalysiert. Es ist zu beobachten, dass im Zuge der Internationalisierung des Einzelhandels die Einzelhändler ihre modernen Managementkonzepte exportieren. In diesem Artikel beschreiben wir den Internationalisierungsprozess des Einzelhandels und die daraus resultierende Veränderungen für die Agrar- und Ernährungswirtschaft. Des Weiteren wenden wir die gewonnen Erkenntnisse auf das russische Agrar- uns Ernährungssektor an. Hierbei zeigen wir zukünftige Entwicklungsmöglichkeiten des russischen Nahrungsmittelsektors im Zusammenhang mit der Internationalisierung des Lebensmitteleinzelhandels auf.
Keywords: 650; Retail internationalization; Russia; supply chain management